1999
DOI: 10.1021/jp984215v
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy Perturbation Study of Octanol/Water Partition Coefficients:  Comparison with Continuum GB/SA Calculations

Abstract: Molecular dynamics (MD) free energy perturbation (FEP) simulations were carried out in order to obtain insights into the structures and dynamics of a series of small organic solutes in water and water-saturated 1-octanol. Relative free energies of solvation were computed for each solute in both solvents, and these results were used to estimate the relative octanol/water partition coefficients (log P o w). The relative octanol/water partition coefficients were in good agreement with experimental log P o w value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 107 publications
8
118
0
1
Order By: Relevance
“…40,41 Finally, the parametrization of a classical version of the GB/SA continuum model has been reported, 42 and its accuracy for predicting log P ow values has been recently summarized by comparison with free energy calculations. 31 In this study we report the parametrization of the HF/6-31G(d) version of the MST continuum model 43 for calculating free energies of solvation in n-octanol and for predicting octanol/water partition coefficients. Several reasons justify our effort.…”
mentioning
confidence: 99%
“…40,41 Finally, the parametrization of a classical version of the GB/SA continuum model has been reported, 42 and its accuracy for predicting log P ow values has been recently summarized by comparison with free energy calculations. 31 In this study we report the parametrization of the HF/6-31G(d) version of the MST continuum model 43 for calculating free energies of solvation in n-octanol and for predicting octanol/water partition coefficients. Several reasons justify our effort.…”
mentioning
confidence: 99%
“…The Gibbs free energy changes were also calculated by the continuum GB/SA models. A comparison of the results that were calculated with the FEP and GB/SA models indicated that for the set of 12 solutes in this study, GB/SA actually yielded more accurate estimates of Δlog P o/w at a significantly lower computational cost (Best et al 1999). Garrido et al computed the Gibbs free energies of solvation for several n-alkanes in 1-octanol and water using three different force fields, namely, Gromos, TraPPE, and OPLS-AA.…”
Section: Lipophilicitymentioning
confidence: 82%
“…The simplicity of the potential energy function of this method makes to run very long simulations properly, in the nano and micro second time scale, and to extract valuable structural information and energy data from trajectories obtained. Other more refined molecular dynamics approaches like MD-FEP allow to calculate absolute enzyme-substrate binding free energies [37]. As a matter of fact, in all these methods it is mandatory to perform a parameterization of the ligand prior to run the molecular dynamics simulations.…”
Section: Computational Modeling Methods In Enzyme-substrate Studiesmentioning
confidence: 99%